The Practice Of Public Relations In Malaysia : A Case Study On The Roles Of Public Relations Practitioners In The Hotel Industry In Penang - Khoo, Gim Hoon (2012)
This is a case study on the roles public relations practitioners enact in the hotel industry. The roles of 23 practitioners were studied using Broom’s (1982) 24-item role typology. The factors influencing practitioners’ role enactment were also investigated. The study employs the survey method and in-depth interview. A survey was conducted to collect data using the purposive sampling method. In January 2009, survey questionnaires were distributed to practitioners in the hotel industry in Penang. Descriptive statistics were used to analyse the data.